Circular economy in the plastic industry: A situational analysis and a strategic action plan - Pérez-Canto, Salvador (Springer Nature, 2026)
The Circular Economy (CE) is a key model for advancing global sustainability within the framework of the United Nations 2030 Agenda for Sustainable Development. Unlike the Linear Economy (LE), which follows a take-make-dispose approach, the CE prioritizes reducing, reusing, and recycling materials. Currently, approximately 42% of global plastic consumption consists of single-use plastics, typically discarded within minutes, while only 9% of all plastics produced historically have been recycled. Separately, just 9% of the global economy operates within circular principles. These figures highlight the urgent need for industries to adopt more responsible and sustainable resource management strategies, as advocated by the CE. The main objective of this study is to evaluate how the principles of the CE can be effectively integrated into the plastic industry to accelerate its green transition. A survey was conducted among industry experts, and the responses were analyzed using Principal Component Analysis (PCA). The findings reveal an increasing commitment to circularity within the plastic sector, driven by innovation, cross-sector collaboration, and alignment with the Sustainable Development Goals (SDGs), ultimately aiming to reduce environmental impact and dependency on non-renewable resources.
This is a post-peer-review, pre-copyedit version of a chapter published by Springer Nature. The final authenticated version is available via the publisher.
Keywords: Plásticos - Industria; Economía circular; Desarrollo sostenible; Circular economy; Sustainability; Green transition; Plastic industry; Principal component analysis; Strategic action plan